Pharmacoeconomic evaluation of follitropin alfa in patient groups with differential ovarian response in assisted reproductive technology programs - A. A. Slabikova; T. S. Teptsova; V. V. Omelyanovskiy; T. A. Nazarenko; N. V. Bashmakova; D. V. Blinov (FARMAKOEKONOMIKA. Modern Pharmacoeconomics and Pharmacoepidemiology, 2026)
Objective : To evaluate the pharmacoeconomic performance of follitropin alfa in women with poor, normal, and high responses to ovarian stimulation in assisted reproductive technology programs. Material and methods . A pharmacoeconomic evaluation was conducted in women with infertility and an anticipated poor ovarian response undergoing in vitro fertilization, using a cost-minimization analysis. The base-case scenario compared follitropin alfa (Gonal-f® – Merck Serono S.p.A., Italy; Primapur® – IVFarma, Russia) with a fixed-dose combination (FDC) of follitropin alfa/lutropin alfa (Pergoveris® – Merck Serono S.A., Succursale d'Aubonne, Switzerland), all of which are included in the national list of vital and essential drugs. A budget impact analysis was performed for the target population of women with differential ovarian response receiving the FDC in conventional stimulation protocols. In addition, the study compared the cost of a stimulation cycle with follitropin alfa versus the FDC and examined cost differences between biosimilars and originator of follitropin alfa. Results . In cost-minimization analysis, the mean cost of a stimulation cycle with follitropin alfa was 27–34% lower than that with the FDC, depending on the dosage. The budget impact analysis showed that switching 70% of patients to follitropin alfa reduced total expenditures by 30–33% relative to current practice. This economic advantage was consistent across women with poor, normal, and high ovarian response. In comparative cost analyses, both biosimilars of follitropin alfa were less expensive than the originator formulation. Conclusion . Use of follitropin alfa, in particular biosimilar formulations, is associated with lower costs than the FDC of follitropin alfa/ lutropin alfa across all evaluated scenarios. These findings support the economic feasibility of incorporating follitropin alfa into assisted reproductive technology programs.